2022
DOI: 10.1108/jm2-02-2022-0045
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the research trends of COVID-19 using topic modeling approach

Abstract: Purpose The COVID-19 pandemic has impacted 222 countries across the globe, with millions of people losing their lives. The threat from the virus may be assessed from the fact that most countries across the world have been forced to order partial or complete shutdown of their economies for a period of time to contain the spread of the virus. The fallout of this action manifested in loss of livelihood, migration of the labor force and severe impact on mental health due to the long duration of confinement to home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…One model often used in topic modelling is Latent Dirichlet Allocation (LDA). The Latent Dirichlet Allocation (LDA) model is a probability model of textual data which can explain the correlation between words and semantic themes hidden in the document [20]. The parameter estimation used in the model is the Bayesian method.…”
Section: Related Workmentioning
confidence: 99%
“…One model often used in topic modelling is Latent Dirichlet Allocation (LDA). The Latent Dirichlet Allocation (LDA) model is a probability model of textual data which can explain the correlation between words and semantic themes hidden in the document [20]. The parameter estimation used in the model is the Bayesian method.…”
Section: Related Workmentioning
confidence: 99%
“…The interrelationships among factors that influence the organizational dynamics to be accounted while starting up new ventures. Practitioners can use this model of Trivedi et al (2022) to further test, validate and prioritize these factors under the impact of pandemic to build concrete roadmap. The practitioners may derive helpful policies from the study of Kumar et al (2022) by designing more resilient and sustainable food supply chains.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…It also helps in setting the preferences among employment alternatives to tech-economical feasibility of stakeholders. Eighth: As the state-of-art base of existing literature lacks the information about research to be conducted upon, Trivedi et al (2022) analysed sources using topic mining approach to identify the same. Though this study contributes very little to the literature, it highlights research issues that need to be addressed in contemporary pandemic time.…”
Section: Contribution Towards Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…LDA, based on the PLSA algorithm and originally proposed by Blei, is an unsupervised machine learning technique for identifying potential topic word information in document sets [4]. LDA topic model has proven to be well adapted in practical applications: for example, Wenjuan Wang and Jianxia Ma [5] used NSF-funded ocean acidification-related project applications and journal papers as research data for topic mining and evolution analysis, and the study found that LDA topic modeling can well mine the main research topics of these projects; Trivedi et al [6] carried out topic modeling on the research trend of the COVID-19 pandemic, and found that LDA topic modeling can help identify heterogeneous topics related to the COVID-19 pandemic other than medical topic. Tan Chunhui et al [7] constructed a sentiment analysis framework combining Baidu's sentiment analysis and LDA topic identification and studied the emotions of social media onlookers in privacy breaches.…”
Section: Research Based On Lda Topic Modelingmentioning
confidence: 99%